2017
DOI: 10.18632/oncotarget.21861
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic performance enhancement of pancreatic cancer using proteomic multimarker panel

Abstract: Due to its high mortality rate and asymptomatic nature, early detection rates of pancreatic ductal adenocarcinoma (PDAC) remain poor.We measured 1000 biomarker candidates in 134 clinical plasma samples by multiple reaction monitoring-mass spectrometry (MRM-MS). Differentially abundant proteins were assembled into a multimarker panel from a training set (n=684) and validated in independent set (n=318) from five centers. The level of panel proteins was also confirmed by immunoassays. The panel including leucine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 53 publications
2
59
0
Order By: Relevance
“…and specificity of 92.1%. 26 Although the origins and functions of LRG1 and transthyretin are unclear, the authors suggested that these proteins are highly relevant to PC. In their study, the target markers were not confined to metabolites, and this triple-marker panel appears to be useful for patients with PC and low CA19-9.…”
Section: Discussionmentioning
confidence: 99%
“…and specificity of 92.1%. 26 Although the origins and functions of LRG1 and transthyretin are unclear, the authors suggested that these proteins are highly relevant to PC. In their study, the target markers were not confined to metabolites, and this triple-marker panel appears to be useful for patients with PC and low CA19-9.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al have verified 176 protein candidates with MRM in 134 clinical samples, and 54 of these were further validated with MRM and ELISA in large‐clinical plasma samples ( n = 1002) from multi‐clinics. In distinguishing PC from normal, benign disease states, and other cancers (colorectal, thyroid and breast cancer), a triple‐marker panel (LRG1, transthyretin (TTR) and CA 19‐9) can have AUC values of 0.931, 0.892 and 0.899, respectively …”
Section: Pancreatic Cancer (Pc)mentioning
confidence: 99%
“…Selected studies of analytically validated protein markers discovered by MS-based proteomics approach for PC BC: benign control and other cancers (colorectal, thyroid and breast cancer), a triplemarker panel (LRG1, transthyretin (TTR) and CA can have AUC values of 0.931, 0.892 and 0.899, respectively 70. …”
mentioning
confidence: 99%
“…Since Pearson's work in 1899, linear regression method has been the most popular way to develop stature estimation equations [13,19,21,[26][27][28][29][30][31]. In general, under an assumption of linearity between variables, linear regression analysis 1) describes a pattern of the relationship in a numeric form and/or 2) predicts one variable from another variable.…”
Section: Application To Extrapolation/extreme Casesmentioning
confidence: 99%